Experimental study of (p, 2p) reactions at 392 MeV on 12C, 16O, 40Ca and 208Pb nuclei leading to low-lying states of residual nuclei. (30th September 2020) - Noro, Tetsuo; Wakasa, Tomotsugu; Ishida, Takashi; Yoshida, Hidetomo P; Dozono, Masahiro; Fujimura, Hisako; Fujita, Kunihiro; Hatanaka, Kichiji; Ishikawa, Takatsugu; Itoh, Masatoshi; Kamiya, Junichiro; Kawabata, Takahiro; et al.
Abstract: We have measured the differential cross-sections and analyzing powers for ($p, 2p$ ) reactions at an incident energy of 392 MeV on $^{12}$ C, $^{16}$ O, $^{40}$ Ca, and $^{208}$ Pb nuclei, leading to discrete states of the residual nuclei. The data are compared with two kinds of distorted-wave impulse approximation (DWIA) calculations, a standard calculation using a global optical potential and a calculation using wave functions generated in a relativistic Hartree model. The spectroscopic factors deduced from these two calculations agree with those determined in ($e, e'p$ ) studies mostly within 15% in the case of the lighter three target nuclei. However, those for the $^{208}$ Pb target are overestimated compared with the ($e, e'p$ ) results. In the heavy target case, the DWIA results are very sensitive to the radius parameter of the bound-state potential and thus a careful treatment is required. Regarding the analyzing powers of the present measurement, we confirmed that the $j$ -dependence is sufficient for practical spectroscopic use.